Activating mutations in Kir6.2 and neonatal diabetes: new clinical syndromes, new scientific insights, and new therapy. - Hattersley, A; Ashcroft, F (2005)
Closure of ATP-sensitive K(+) channels (K(ATP) channels) in response to metabolically generated ATP or binding of sulfonylurea drugs stimulates insulin release from pancreatic beta-cells. Heterozygous gain-of-function mutations in the KCJN11 gene encoding the Kir6.2 subunit of this channel are found in approximately 47% of patients diagnosed with permanent diabetes at <6 months of age. There is a striking genotype-phenotype relationship with specific Kir6.2 mutations being associated with transient neonatal diabetes, permanent neonatal diabetes alone, and a novel syndrome characterized by developmental delay, epilepsy, and neonatal diabetes (DEND) syndrome. All mutations appear to cause neonatal diabetes by reducing K(ATP) channel ATP sensitivity and increasing the K(ATP) current, which inhibits beta-cell electrical activity and insulin secretion. The severity of the clinical symptoms is reflected in the ATP sensitivity of heterozygous channels in vitro with wild type > transient neonatal diabetes > permanent neonatal diabetes > DEND syndrome channels. Sulfonylureas still close mutated K(ATP) channels, and many patients can discontinue insulin injections and show improved glycemic control when treated with high-dose sulfonylurea tablets. In conclusion, the finding that Kir6.2 mutations can cause neonatal diabetes has enabled a new therapeutic approach and shed new light on the structure and function of the Kir6.2 subunit of the K(ATP) channel.